Preoperative Prediction of the Difficulty of Laparoscopic Cholecystectomy - Aly Saber; Sameh T Abu-Elela; Khaled M shaalan; Adel R Al-Masry (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Introduction: Preoperative complexity estimation helps deciding whether to proceed with a minimally invasive approach, perform an open procedure or make a referral to a more experienced surgeon. Laparoscopic cholecystectomy outcome is particularly affected by the presence and severity of inflammation, advancing age, male sex and greater BMI. Objective: The aim was to trace outcome of laparoscopic cholecystectomy with difficult situation. Patients and Methods: A total of 204 patients with difficult situation cholecystitis were enrolled to this study. The triad of clinical examination, laboratory data and ultrasound study was preformed for all patients. The primary end point of the study was operative outcome and the second end point was morbidity related to surgery. Results: The operative outcome was represented as operative bleeding and conversion to open surgery while the postoperative outcome was biliary leakage and port site infection. The total score for each patient with conversion to open surgery or with postoperative biliary leakage was between 6-10 points indicating difficult surgical approach according to the scoring system. Conclusion: Preoperative prediction of risk factors of conversion or difficulty is an important point for operative planning and the high risk patients may be informed accordingly.